Serologic and molecular detection of porcine reproductive and respiratory syndrome virus in plasma of domestic pigs from selected backyard farms in Luzon, Philippines - Bernardo, John Michael G.; Vergara, Emil Joseph S.; Pangga, Gladys Maria V.; Collantes, Therese Marie A. (2022)
As a notifiable disease in the Philippines, porcine reproductive and respiratory syndrome (PRRS) surveillance and risk assessment is necessary at the farm and regional levels. This study primarily aimed to detect anti-PRRSv antibodies using indirect enzyme-linked immunosorbent assay (ELISA) and viral nucleic acids using conventional reverse transcriptase polymerase chain reaction (RT-PCR) in plasma of domestic pigs from selected backyard farms in selected provinces in Luzon, Philippines. A total of 382 individual and 117 pooled samples were subjected to ELISA and RT-PCR, respectively. Overall, ELISA results showed 5.50% seropositivity, with Bulacan (32.14%) and Cagayan (7.25%) having the highest positivity rates. Using RT-PCR, 5.98% of pooled samples, specifically from Batangas, Marinduque, and Cagayan, tested positive for PRRS viral nucleic acids. Using binary logistic regression, respiratory symptoms were more likely to be associated with PRRS positivity in ELISA and PCR (p<0.05). The results suggest persistent PRRS challenge in provinces with positive outcomes in the assays, warranting the need for improvement in PRRS monitoring in the Philippines.
Keywords: Swine; Communicable diseases in animals; PRRS